Sex, Services, and Surveillance: The Cleveland Street Scandal Revisited - Hindmarch-Watson, Katie (History compass, 2016)
The 1889 "Cleveland Street Scandal" in London, which exposed a male brothel offering telegraph boys to elite men for sexual services, has long been recognized and evaluated as a window into late Victorian homoerotic subcultures and regulatory legislation. By focusing on the telegraph boys' contribution to the scandal, particularly their roles as information service providers in relation to the broader ideologies associated with telecommunications work in this period, the scandal takes on new meanings for queer history. It reveals the relationship between queer urban encounters and the growth of clandestine communications surveillance in Britain and opens up possibilities for re-prioritizing service labor in historical accounts of queer interactions and subjectivities.